Acetate degradation at low pH by the moderately acidophilic sulfate reducer Acididesulfobacillus acetoxydans gen. nov. sp. nov. - Sánchez-Andrea, Irene (2022)
The Supplementary Material for this article can be found online at: https://www.frontiersin.org/articles/10.3389/fmicb.2022.816605/full#supplementary-material